Transfer of Drought Resistant Character from Wild Rice (Oryza meridionalis and Oryza nivara) to Cultivated Rice (Oryza sativa L.) by Backcrossing and Immature Embryo Culture - Pham Thien Thanh; Prapa Sripichitt; Sontichai Chanprame; Surin Peyachoknagul (Agriculture and Natural Resources, 2006)
Drought is an abiotic stress to be continuing threat to rice production. The characteristics supporting to drought resistance are restricted in cultivars while wild species of Oryza are an important reservoir of useful genes for rice improvement. The objective of this study was to transfer drought resistant character from wild species (O. meridionalis and O. nivara) to cultivated rice varieties RD23 and CN1 by backcrossing in combination with immature embryo culture. Hybridization between cultivated rice and wild species was made to produce six interspecific hybrid crosses. Crossability between cultivated rice and wild species of all crosses varied from 21.2 to 50% with an average of 35.3%. The F1 hybrid embryos obtained were rescued by culturing on the half-strength MS medium. Germination ability of the hybrid embryos of all crosses ranged from 36.2 to 62.1% with an average of 52.0%. The F1 hybrid plants obtained showed low pollen fertility and relatively poor agronomic characters. They were then backcrossed to their cultivated recurrent parents to restore fertility and good agronomic performance from cultivated rice. The 299 BC1F1 plants were produced from six backcrosses of which 235 plants could set BC1F2 seeds. The 452 BC1F2 progenies from six backcrosses were screened for drought resistance at vegetative growth stage by visual scoring of leaf rolling, leaf drying and plant recovery. Selection was made for 39 BC1F2 plants resistant to drought and having high seed yield per plant and good agronomic performance. They will be grown to be BC1F3 lines for further evaluation on drought resistance, yield and agronomic performance.